A multi-laboratory comparison of two molecular methods for the detection of toxigenic Clostridium difficile - Diane C Halstead; Joan Abid; Lynne Sloan; Diana Meza; Daphne Ramsey-Walker; Donna Jane Hata (Journal of Infection in Developing Countries)
Introduction: Diarrheal disease due to toxigenic Clostridium difficile (CD) accounts for an increased number of hospitalizations and deaths each year. Published guidelines recommend reflex testing of CD antigen-positive samples to molecular testing or testing samples directly by a molecular assay. This multicenter study was designed to compare the accuracy of two different molecular methods targeting different CD genes: Xpert C. difficile Epi RUO RT-PCR assay (XPCR) which targets toxin B (Cepheid, Sunnyvale, CA) and a laboratory-developed PCR (LDPCR) which targets mutations in the tcdC regulatory gene. Methodology: Two molecular methods for toxigenic CD detection, the Xpert C. difficile Epi RUO RT-PCR assay (XPCR) [Cepheid, Sunnyvale, CA] and a laboratory-developed PCR assay (LDPCR) were compared to a consensus gold standard (CGS) or toxigenic culture (TC) as the reference method. A subset of specimens was subjected to additional molecular characterization of toxigenic CD. Results: Both molecular methods were >90% sensitive for CD detection. Discordant results were noted when molecular test results were compared to non-molecular methods. Supplemental molecular characterization illustrated inherent difficulties in comparisons using different molecular methods for CD. Conclusion: Laboratories may consider using multiple CD detection methods or combinations of methods, including molecular detection for rapid and accurate diagnosis of CD, as driven by best practices for the respective healthcare environment. Laboratories must be aware of intrinsic differences when comparing performance characteristics of different molecular assays.